The safety and effectiveness of HBV vaccination in patients with juvenile idiopathic arthritis controlled by treatment. Issue 3 (3rd May 2016) - Nerome, Yasuhito; Akaike, Harumi; Nonaka, Yukiko; Takezaki, Tomoko; Kubota, Tomohiro; Yamato, Tsuyoshi; Yamasaki, Yuichi; Imanaka, Hiroyuki; Kawano, Yoshifumi; Takei, Syuji
Abstract: Objectives : To evaluate the safety and effectiveness of hepatitis B virus (HBV) vaccination in patients with juvenile idiopathic arthritis (JIA) controlled by treatment. Methods : Among 49 patients with juvenile idiopathic arthritis (JIA) at the outpatient clinic of Kagoshima University Hospital, we enrolled 25 who were controlled by treatment. All children were unimmunized and were vaccinated against HBV according to the schedule. Their responses to the vaccine and vaccine adverse events were examined during their visits. Results : Nineteen of the 25 patients with JIA controlled by treatment developed effective antibody responses (76%). All eight patients with JIA below 10 years of age achieved seroconversion. The seroconversion was not influenced by biologics. Five adverse events were observed (6.7%). The rate of all adverse events did not surpass that of a previous report, and all adverse events were immediately resolved. None of the patients with JIA experienced a flare-up or clinical deterioration related to the vaccination. Conclusions : HBV vaccination is safe and effective. Pediatric rheumatologists should consider HBV vaccination for unimmunized patients with JIA, because the response to HBV vaccine might be influenced by age, and children have a higher risk for potential HBV infection than adults.